Hidrocarbonetos policíclicos aromáticos em café torrado: otimização e validação de método por cromatografia a gás acoplada a espectrometria de massas - Rafael Pissinatti (2013)
Polycyclic aromatic hydrocarbons (PAHs) comprise a class of organic compounds generated from incomplete combustion or pyrolysis of organic matter, and may present carcinogenic properties. The presence of PAHs in coffee can be attributed to the contamination of green beans and, mainly, to the formation during drying and roasting. The coffee importance for Brazil is notorious, especially considering that ths country is the world's largest producer and second largest consumer in terms of absolute consumption. For this reason, a method for determination of priority PAHs in roasted coffee was optimized and validated by in-house procedures. Parameters for pressurized liquid extraction and purification were optimized. For detection and quantification gas chromatography coupled to mass spectrometry was employed. The selectivity was compromised for the lower molecular weight and lower toxicity analytes: naphthalene, acenaphthylene, acenaphthene, fluorene, phenanthrene and anthracene. Linearity, in accordance to all premises of simple linear regression, was obtained in the concentration range from 0.25 to 4.00 g/kg. Matrix effects were not significant, except for naphthalene and acenaphthylene. The precision was adequate under conditions of intermediate precision and repeatability with relative standard deviation varying entre 3.26 and 23.75% and between 3.29% and 33.34%, respectively. The values of average recoveries ranged from 87.08 to 111.28%. These values, as well as the limits of detection, limits of quantification and uncertainties of measurements met the performance criteria established by the European Union regulations. The method was applied for the analysis of commercial samples. One of the three brands tested showed contamination up to 11.29 ± 2.33 mg/kg for the sum of PAHs. These results indicated the need of future researches to establish the critical points for the contamination of the Brazilian roasted coffee with PAH, as well the adoption of control and monitoring actions.